1981
DOI: 10.1111/j.1532-5415.1981.tb01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Senile Dementia: Combined Pharmacologic and Psychologic Treatment

Abstract: Either supportive counseling (SC) or cognitive training (CT) was used in an attempt to enhance the efficiency of a standard pharmacologic treatment for dementia, viz, dihydroergotoxine mesylate (DEM, Hydergine). DEM was administered orally to 21 moderately demented subjects, in a dosage of 1 mg three times daily; and SC or CT was conducted for one hour every two weeks for a total of 12 weeks. The CT was designed to enhance memory and other intellectual functions by the teaching of organizational schemes and mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 23 publications
(22 reference statements)
0
17
0
1
Order By: Relevance
“…Among more 'cognitive-specific' intervention we can consider techniques of cognitive remediation and training, which are based on stimulation of functions relatively spared in the first phases of AD. Some reports of positive results can be found in literature for these techniques (Beck, Heacock, Mercer, Thatcher, & Sparkman, 1988;McEvoy & Patterson 1986;Yesavage, Westphal, & Rush, 1981;Zarit, S.H., Zarit, J.M., & Reever, 1982), but, again, results were not conclusive (Clare, Woods, Moniz Cook, Orrell, & Spector, 2003).…”
mentioning
confidence: 78%
“…Among more 'cognitive-specific' intervention we can consider techniques of cognitive remediation and training, which are based on stimulation of functions relatively spared in the first phases of AD. Some reports of positive results can be found in literature for these techniques (Beck, Heacock, Mercer, Thatcher, & Sparkman, 1988;McEvoy & Patterson 1986;Yesavage, Westphal, & Rush, 1981;Zarit, S.H., Zarit, J.M., & Reever, 1982), but, again, results were not conclusive (Clare, Woods, Moniz Cook, Orrell, & Spector, 2003).…”
mentioning
confidence: 78%
“…Clinical studies have indicated improved cognitive function in relation to patients under placebo [21,22], Nootropic substances and enhancers of brain activity such as pyritinol [23,24] are often used for symptomatic treatment of AD, and they may be effective by their acti vation of brain metabolism. In analogy to the positive influence of memory training on forgetfulness in higher age [25], cognitive training programs may also be utilized in AD, and their efficacy might be enhanced by drugs sta bilizing neuronal metabolism [26]. Therefore, a con trolled parallel group pilot study was designed in which the effectiveness of PS plus cognitive training was com pared with cognitive training alone, cognitive training plus pyritinol, and with social support alone.…”
mentioning
confidence: 99%
“…Further, she or he needs to remember the strategy over some significant period of time. Thus, it is not surprising that research has typically shown negative results when these strategies have been applied to persons with adementing disorder (Becket al, 1985;Yesavage et al, 1981;Zarit et al, 1982).…”
Section: Supporting Everyday Activities In Dementia Staffan Josephssonmentioning
confidence: 96%